Land, Ethnicity and Political Legitimacy in Eastern Sudan (Kassala & Gedaref States) - Ireton, François; Dalmau, Isabelle; Miller, Catherine (Le Caire : CEDEJ, Khartoum : DSRC, University of Khartoum, 2005)
General presentation
Miller, Catherine - Power, land and ethnicity in the Kassala-Gedaref States
Ireton, François - A demographic profile of Kassala and Gedaref States
Political and economical dynamics
Ahmed, Einas - Political dynamics and the search for legitimacy at the local level : the case of Kassala State
El Obeid, Amani M. - Sufi brotherhoods in Kassala and Gedaref States
Delmet, Christian - The native administration system in eastern Sudan : from its liquidation to its revival
Assal, Munzoul A. M. - Economy and politics in Gedaref : a symbiotic encounter
Dalmau, Isabelle - Camel production and trade in eastern Sudan : a case study of Showak Market
Ireton , François - Literacy in the States of Kassala and Gedaref : gender, spatial and generational inequalities
History of population and ethnic construction
Bushra, Eman - Local-level political dynamics in Kassala State : the Rashayda
Khalid, Tamadur - Dalmau, Isabelle - Miller, Catherine - The Lahawiyyin in Showak Rural Council : imposed boundaries and the quest for political recognition
Casciarri, Barbara - Dynamics of tribal recomposition in a nomadic arab population : the case of the Ahamba
Abu Manga, Al-Amin - Miller, Catherine - The West African (Fallata) communities in Gedaref State : process of settlement and local integration
Hasterok, Rupert - Sultan Muhammad Belo Mai Wurno, native administration and the Fallata of Kassala Province
Khalid, Tamadur - Dynamics of change in gender relations among the Lahawiyyin pastoral community
Hamid, Mohammed Tahir - Ethics and oral poetry in Beja society
Notes, bibliogr., glosssaire
0015